Optimal. Leaf size=24 \[ e^{2+\frac {-1+x+\frac {\log (x)}{2 x-\log (x)}}{x}} \]
________________________________________________________________________________________
Rubi [F] time = 4.30, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right ) \left (2 x+4 x^2-8 x \log (x)+2 \log ^2(x)\right )}{4 x^4-4 x^3 \log (x)+x^2 \log ^2(x)} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {2 \exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right ) \left (x+2 x^2-4 x \log (x)+\log ^2(x)\right )}{x^2 (2 x-\log (x))^2} \, dx\\ &=2 \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right ) \left (x+2 x^2-4 x \log (x)+\log ^2(x)\right )}{x^2 (2 x-\log (x))^2} \, dx\\ &=2 \int \left (\frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{x^2}+\frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right ) (1-2 x)}{x (2 x-\log (x))^2}\right ) \, dx\\ &=2 \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{x^2} \, dx+2 \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right ) (1-2 x)}{x (2 x-\log (x))^2} \, dx\\ &=2 \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{x^2} \, dx+2 \int \left (-\frac {2 \exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{(2 x-\log (x))^2}+\frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{x (2 x-\log (x))^2}\right ) \, dx\\ &=2 \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{x^2} \, dx+2 \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{x (2 x-\log (x))^2} \, dx-4 \int \frac {\exp \left (\frac {2 x-6 x^2+(-2+3 x) \log (x)}{-2 x^2+x \log (x)}\right )}{(2 x-\log (x))^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 1.65, size = 19, normalized size = 0.79 \begin {gather*} e^{3-\frac {2}{x}-\frac {2}{-2 x+\log (x)}} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.63, size = 33, normalized size = 1.38 \begin {gather*} e^{\left (\frac {6 \, x^{2} - {\left (3 \, x - 2\right )} \log \relax (x) - 2 \, x}{2 \, x^{2} - x \log \relax (x)}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.24, size = 71, normalized size = 2.96 \begin {gather*} e^{\left (\frac {6 \, x^{2}}{2 \, x^{2} - x \log \relax (x)} - \frac {3 \, x \log \relax (x)}{2 \, x^{2} - x \log \relax (x)} - \frac {2 \, x}{2 \, x^{2} - x \log \relax (x)} + \frac {2 \, \log \relax (x)}{2 \, x^{2} - x \log \relax (x)}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.03, size = 32, normalized size = 1.33
method | result | size |
risch | \({\mathrm e}^{\frac {3 x \ln \relax (x )-6 x^{2}-2 \ln \relax (x )+2 x}{x \left (\ln \relax (x )-2 x \right )}}\) | \(32\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.50, size = 20, normalized size = 0.83 \begin {gather*} e^{\left (\frac {2}{2 \, x - \log \relax (x)} - \frac {2}{x} + 3\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 5.64, size = 55, normalized size = 2.29 \begin {gather*} x^{\frac {3\,x-2}{x\,\ln \relax (x)-2\,x^2}}\,{\mathrm {e}}^{-\frac {6\,x^2}{x\,\ln \relax (x)-2\,x^2}}\,{\mathrm {e}}^{\frac {2\,x}{x\,\ln \relax (x)-2\,x^2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.44, size = 27, normalized size = 1.12 \begin {gather*} e^{\frac {- 6 x^{2} + 2 x + \left (3 x - 2\right ) \log {\relax (x )}}{- 2 x^{2} + x \log {\relax (x )}}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________